GAMBARAN TINGKAT PENGETAHUAN PASIEN RAWAT JALAN UMUM TENTANG PENGGUNAAN AMOKSISILIN DI PUSKESMAS DONO KABUPATEN TULUNGAGUNG - Djembor Sugeng Walujo; Indah Sri Hartini; Yogi Bhakti Marhenta; Wika Atmaja; Krisogonus Ephrino Seran; Hariyani Hariyani; Fitria Wahyuning Wulan; Aditha Nur Azizah (JURNAL PHARMA BHAKTA, 2026)
Background: Irrational use of antibiotics, including amoxicillin, contributes to the increase in bacterial resistance and the risk of adverse drug reactions. Adequate patient knowledge is a key factor in promoting appropriate antibiotic use. Objective: To describe the level of knowledge among general outpatients regarding the use of amoxicillin at Dono Public Health Center, Tulungagung Regency. Methods: This study used a descriptive quantitative design with sampling involving 85 respondents who had previously received an amoxicillin prescription. Data were collected using a structured questionnaire consisting of 12 items covering nine knowledge parameters: drug classification, administration rules, dosage, adherence to schedule, appropriate indications, duration of use, legal access, side effects, and common misconceptions. Results: The results showed that 52.94% of respondents had a moderate level of knowledge, 36.47% had a good level of knowledge, and 10.59% had a poor level of knowledge. The highest knowledge score was found in the classification parameter (98.82%), while the lowest scores were in side effects (48.24%) and common misconceptions (49.41%). Conclusion: Patients generally demonstrated adequate knowledge of the basic aspects of amoxicillin use; however, gaps remain in understanding the risks of resistance, side effects, and appropriate indications. Strengthening education and implementing continuous interventions are essential to encourage rational antibiotic use.